Improved self-powered system capable of synchronously and persistently desulfurizing and efficiently producing hydrogen
Through the FeMo2S4/NiSX/NF catalyst and zinc air battery self-electric system, the problem of low catalyst activity and stability in the self-driven SOR||HER coupling system is solved, and efficient hydrogen production and sulfur resource recycling are achieved, reducing energy consumption and passivation phenomenon significantly improves the energy efficiency of the system.
Patent Information
- Application Number
- CN202411012611.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-26
- Publication Date
- 2024-12-13
AI Technical Summary
The prior art has problems with low catalyst activity and stability in the self-driven SOR||HER coupling system, especially due to the adsorption of polysulfide intermediates, and the development of three-function catalysts is difficult, resulting in H2 production. Insufficient efficiency and S recovery sustainability.
FeMo2S4/NiSX/NF materials are used as three-function catalysts, and the hydrogen production and desulfurization functional system is driven by the zinc-air battery self-electric system. NaOH and Na2S are used to simulate sulfur-containing wastewater to achieve hydrogen production and sulfur ion removal, and a collaborative engineering design combining Mo and Fe , regulate the interface interaction between the catalyst and sulfide, promote sulfur dissolution and form long-chain polysulfides, and avoid passivation.
Efficient and long-lasting hydrogen production and sulfur resource recycling have been achieved. The catalysts show long-term stability in SOR and HER reactions, reduce the demand for applied potential, reduce energy consumption to 28%, and the hydrogen production rate reaches 7.89mmol min-1gcatalyst- 1. Significantly improve the energy efficiency of the system.
Smart Images

Figure CN119133728A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sewage treatment and hydrogen production by electrolysis of water, and specifically relates to an improved self-powered system for synchronous and durable desulfurization and efficient hydrogen production. Background Art
[0002] In recent years, the rapid development of human society has caused the depletion of fossil fuels and the intensification of environmental problems. On the one hand, the widespread use of Na2S reagents in industries such as papermaking, leather manufacturing, dyeing and printing has led to increased sulfide concentrations in wastewater. The production and disposal of these toxic substances pose a major threat to human health and the environment. On the other hand, the rapid growth of the world's population and industrialization have increased global energy demand, and sustainable and environmentally friendly renewable energy carriers are urgently needed.
[0003] So far, there is still room for improvement in the research of self-driven SOR||HER coupling system: in the process of single sulfur oxidation reaction, sulfur passivation is an important factor that hinders the efficient sulfur oxidation reaction in electrochemical desulfurization and resource recovery of sulfur-containing pollutants. The polysulfide intermediates adsorbed on the catalyst surface have strong affinity, which will greatly reduce the activity and stability of the catalyst, which further increases the design difficulty; the development of trifunctional catalysts with multiple active components and interfaces supporting three-phase reactions is extremely difficult, and the progress of this technology is hindered by the limited availability of reasonably priced, efficient and stable catalysts; previous studies have gotten rid of the dependence on the functional end to achieve complete self-sufficiency of the system, and the overall self-driven hydrogen production rate reached 5.20mmol min -1 g catalyst -1 , it is extremely challenging to achieve more efficient H2 production and more sustainable S recovery. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide an improved self-powered system for synchronous and durable desulfurization and efficient hydrogen production.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: an improved synchronous and durable desulfurization and efficient hydrogen production self-powered system, comprising:
[0008] The self-powered system comprises:
[0009] Constructing a zinc-air battery self-power system (100), which is composed of a zinc anode (101), an air cathode (102), an electrolytic cell (103) and an electrolyte (104);
[0010] A hydrogen production and desulfurization functional system (200) is constructed, which is composed of an anode electrode (201), a cathode electrode (202), an anode chamber (203), a cathode chamber (204) and a Na ion exchange membrane (205), using NaOH as a cathode liquid, and using NaOH and Na2S to simulate sulfur-containing wastewater as an anode liquid;
[0011] The zinc-air battery self-power system (100) generates a discharge current through an oxygen reduction reaction at an air cathode (102) and an oxidation reaction at a zinc anode (101), and drives a hydrogen production and desulfurization function system (200) to achieve hydrogen production and sulfur ion removal and resource recovery of S;
[0012] The anode electrode (201) and the cathode electrode (202) are both FeMo2S4 / NiS X / NF materials, which have redox, sulfur oxidation and hydrogen evolution reaction activities;
[0013] The air cathode (102) is made of FeMo2S4 / NiS X Prepared from powder.
[0014] As a preferred embodiment of the method of the present invention, the FeMo2S4 / NiS X The preparation method of the / NF electrode comprises:
[0015] Pretreatment of nickel foam: Cut the nickel foam with a thickness of 0.15-0.2 cm into 1×1 cm -2 rectangular pieces, respectively, at 2 to 3 mol L -1 After ultrasonic treatment in HCl solution, acetone, ethanol and deionized water for 20-40 minutes and vacuum drying at 50-60°C, the surface exhibits a silver-grey metallic luster;
[0016] Preparation of FeMoO4 / NF: 400 mg to 600 mg of molybdenum salt and 300 mg to 500 mg of iron salt were added to 30 mL to 50 mL of deionized water, and ultrasonically dispersed (20 to 30 min) and stirred (20 to 30 min) to obtain a uniform solution containing iron and molybdate;
[0017] Then, the dispersed solution and the pretreated nickel foam were transferred into a Teflon-lined stainless steel autoclave reactor (50 mL), the autoclave was sealed, and the temperature was kept at 130-160 °C for 4-6 h;
[0018] After naturally cooling to room temperature, the nickel foam was taken out and washed with deionized water and ethanol, and then vacuum dried at 40-60° C. for 2-3 h to obtain the precursor product FeMoO4 / NF.
[0019] FeMo2S4 / NiS X Preparation of / NF: 300 mg to 500 mg of sulfur-containing compound is dispersed in 30 mL to 50 mL of deionized water;
[0020] The dispersed solution and FeMoO4 / NF were transferred to an autoclave reactor, sealed and placed in an oven for vulcanization treatment at a constant temperature of 140-160°C for 6-8h;
[0021] After cooling naturally to room temperature, the sample was taken out and washed with deionized water and ethanol, and then dried in vacuum at 40-60 °C for 2-3 h to obtain the final product FeMo2S4 / NiS X / NF.
[0022] As a preferred embodiment of the method of the present invention, the FeMo2S4 / NiS X The powder, the preparation method of which comprises,
[0023] FeMo2S4 / NiS X / NF was scraped or ultrasonically treated to obtain FeMo2S4 / NiS X powder.
[0024] As a preferred embodiment of the method of the present invention, the method for preparing the air cathode (102) comprises:
[0025] FeMo2S4 / NiS X The powder was ultrasonically dispersed in a mixed solution of deionized water, isopropanol and Nafion to prepare ink;
[0026] The ink is evenly dropped onto the surface of the hydrophobic carbon paper of the gas diffusion layer, and after drying, the air anode of the zinc-air battery is obtained;
[0027] Among them, FeMo2S4 / NiS X The ratios of powder, deionized water, isopropanol and Nafion solution were 15-25 mg: 360-380 μL, 120-140 μL and 10-20 μL, respectively.
[0028] As a preferred embodiment of the method of the present invention, the preparation method of the zinc anode (101) comprises grinding and polishing a zinc sheet with sandpaper to obtain a cathode electrode of a zinc-air battery.
[0029] As a preferred embodiment of the method of the present invention, the electrolyte (104) is a mixed solution of KOH and Zn(OAc)2.
[0030] As a preferred embodiment of the method of the present invention, the molar concentrations of the KOH and Zn(OAc)2 solutions are 5-7M and 0-1M respectively.
[0031] As a preferred embodiment of the method of the present invention, the iron salt is one or more of Fe(NO3)3·9H2O, FeCl3·6H2O, FeCl2·4H2O, and Fe2(SO4)3·9H2O;
[0032] The molybdenum salt is K2MoO4, Na2MoO4·2H2O, (NH4)6Mo7O 24 ·One or more of 4H2O;
[0033] The sulfur-containing compound is one or more of Na2S, C2H5NS, and CH4N2S.
[0034] As a preferred embodiment of the method of the present invention, the iron salt is ferrous chloride tetrahydrate, and the molybdenum salt is sodium molybdate dihydrate.
[0035] As a preferred embodiment of the method of the present invention, wherein: the NaOH and Na2S simulate sulfur-containing wastewater, wherein the volume molar concentration of the mixed solution of NaOH and Na2S is 0.5-1.5M
[0036] As a preferred embodiment of the method of the present invention, wherein: the NaOH is used as the cathode liquid, wherein the molar concentration of the NaOH solution is 0.5-1.5M, and the molar concentration of the Na2S solution is 0.5-1.5M.
[0037] Beneficial effects of the present invention:
[0038] (1) The present invention aims to treat the highly toxic and environmentally polluting sulfur-containing wastewater, and efficiently produce hydrogen without any external energy consumption, while recovering sulfur. This represents a new and environmentally friendly electrochemical desulfurization hydrogen production method, and paves the way for the advancement of self-sufficient green hydrogen production and integrated energy conversion systems.
[0039] (2) The present invention aims at the passivation problem in the SOR process. According to research, molybdenum sulfide has a sulfur adsorption Gibbs free energy close to thermal neutrality and the ability to quickly convert polysulfide. By introducing Mo, the interface interaction between the catalyst and the sulfide is carefully adjusted to promote the dissolution of the product sulfur on the electrode surface in the electrolyte and convert it into long-chain polysulfide, effectively avoiding the passivation phenomenon. The results show that the electrode has an extraordinary long-term stability (480h) in SOR.
[0040] (3) The present invention aims to solve the problems of high cost and incompatibility of multiphase interfaces of traditional electrocatalysts by carefully designing FeMo2S4 / NiS X / NF trifunctional catalyst. Low-priced iron and molybdenum metals are preferred to greatly reduce costs; Mo and Fe synergistically engineered NiS based on the built-in electric field, adsorption intermediates and broadband center theory are designed. X The hierarchical coupling interface and the multi-interface will promote charge transfer and generate abundant active sites, thus producing a synergistic effect on the electrocatalytic reaction. The results show that the electrode material has a high sulfur oxidation reaction (SOR, η 100 =0.313V) and hydrogen evolution reaction (HER, η 100 =0.148V) activity.
[0041] (3) In view of the self-driving system that has been reported, this paper proposes a strategy to reduce the intrinsic limitations of the hydrogen production and desulfurization functional coupling reaction, and carefully designs the FeMo2S4 / NiS X / NF significantly reduces the required applied potential, which is undoubtedly beneficial to reduce energy consumption and improve the energy efficiency of the overall reaction. The results show that the overall coupling reaction only requires an ultra-low applied potential of 0.53V to achieve 100mA cm -2 The current density is significantly lower than our previous report (0.69 V), the energy consumption is reduced to 28%, and the hydrogen production rate reaches an astonishing 7.89 mmol min -1 g catalyst -1 , laying a solid foundation for the improvement of self-electricity-synchronous efficient sulfur removal and hydrogen production process. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0043] Figure 1 Schematic diagram of the zinc-air battery power system-hydrogen production and desulfurization system in an embodiment of the present invention.
[0044] Figure 2 The system physical diagram, hydrogen production diagram and hydrogen production physical diagram in the embodiment of the present invention are shown; wherein, Figure 2 (a) FeMo2S4 / NiS X / NF is a photo of a self-driven hydrogen production and desulfurization system constructed with a trifunctional catalyst. Figure 2 (b) is a graph showing the hydrogen production in the system over time. Figure 2 (c) is the actual picture of hydrogen production.
[0045] Figure 3 In the embodiment of the present invention, FeMo2S4 / NiS X / NF-1-3 and platinum carbon sulfur oxidation (SOR) linear sweep voltammetry test diagram and hydrogen evolution reaction (HER) linear sweep voltammetry test diagram; Among them, Figure 3 (a) FeMo2S4 / NiS X / NF-1-3, Pt-C and CuMoS / NiS X Sulfur oxidation (SOR) linear sweep voltammetry test diagram of / NF, Figure 3 (b) FeMo2S4 / NiS X / NF-1-3, Pt-C and CuMoS / NiS X Linear sweep voltammetry test diagram of hydrogen evolution reaction (HER) of / NF.
[0046] Figure 4 The FeMo2S4 / NiS X / XRD test pattern of NF-1-3.
[0047] Figure 5 is a SEM image of the catalyst in the embodiment of the present invention; wherein, Figure 5 (a) FeMo2S4 / NiS X / High-magnification SEM image of NF-1 catalyst, Figure 5 (b) FeMo2S4 / NiS X / High magnification SEM image of NF-2 catalyst, Figure 5 (c) FeMo2S4 / NiS X High magnification SEM image of / NF-3 catalyst.
[0048] Figure 6 In the embodiment of the present invention, FeMo2S4 / NiS X / NF's SOR stability test chart and HER stability test chart.
[0049] Figure 7 FeMo2S4 / NiS X / NF is a comparison diagram of the LSV curves of the SOR||HER coupling of the hydrogen production and desulfurization system and the OER||HER coupling of traditional water electrolysis for hydrogen production. DETAILED DESCRIPTION
[0050] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0051] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0052] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0053] The present invention provides an improved self-powered system for synchronous and durable desulfurization and efficient hydrogen production, the main steps of which include:
[0054] (1) Construction of self-driven hydrogen production and desulfurization system: The integrated self-driven coupling system consists of two parts, namely the power system constructed by zinc-air battery and the hydrogen production and desulfurization functional system constructed by sulfur oxidation reaction-hydrogen evolution reaction (SOR||HER), in which the SOR terminal electrode is connected to the zinc anode and the HER terminal electrode is connected to the air cathode.
[0055] Three-phase electrolyte-catalyst-air interface loaded with efficient FeMo2S4 / NiS X The oxygen in the air undergoes an oxidation-reduction reaction (ORR) at the three-phase interface, and the OH generated by the oxidation of the metal zinc - , relying on electrolyte conduction, and the released electrons form a discharge current in the external circuit.
[0056] Driven by the electric power of the zinc-air battery power system, the SOR||HER coupling system undergoes a sulfur oxidation reaction (SOR) at the anode to remove sulfur ions and increase the resources into S element; a hydrogen evolution reaction (HER) occurs at the cathode to generate H2.
[0057] Unless otherwise specified, the raw materials used in the examples of the present invention are commercially available.
[0058] Table 1
[0059] name Commercial channels Part Number Nickel Foam(NF) Hefei Kejing Materials Technology Co., Ltd. G240624F-1 Sodium molybdate dihydrate Sinopharm Chemical Reagent Co., Ltd. C10019818 Ferrous chloride tetrahydrate Sinopharm Chemical Reagent Co., Ltd. XW134781093
[0060] Example 1
[0061] This embodiment provides an improved self-powered system for synchronous and durable desulfurization and efficient hydrogen production. Figure 1 , including a zinc-air battery power system and a hydrogen production and desulfurization functional system. The zinc-air battery power system uses oxygen in the air as the only fuel to drive the hydrogen production and desulfurization functional system to achieve more efficient hydrogen production and more sustainable S resource recovery.
[0062] Specifically, the zinc-air battery power system is composed of a zinc anode, an air cathode, an electrolytic cell and an electrolyte;
[0063] Furthermore, the preparation method of the zinc anode is: a zinc sheet with a thickness of 300 μm is polished with sandpaper for 5 minutes to obtain an anode electrode of a zinc-air battery.
[0064] A zinc-air battery self-power system (100) is composed of a zinc anode (101), an air cathode (102), an electrolytic cell (103) and an electrolyte (104);
[0065] The hydrogen production and desulfurization functional system (200) is composed of an anode electrode (201), a cathode electrode (202), an anode cavity (203), a cathode cavity (204) and a Na ion exchange membrane (205).
[0066] The preparation method of the air cathode is as follows:
[0067] Take 20mgFeMo2S4 / NiS X The powder was evenly dispersed in a mixture of 375 μL of deionized water, 125 μL of isopropanol, and 20 μL of Nafion and ultrasonicated for 30 min to prepare a mixture;
[0068] Then, 100 μL of the mixture was evenly drop-coated onto the surface of a 1.0×1.0 cm carbon paper with a gas diffusion layer, and the electrode was dried at 60°C for 6 hours to prepare the air cathode of the zinc-air battery;
[0069] A ventilation hole was provided at the cathode end and a liquid inlet was provided at the upper end. A mixed solution of 6M KOH and 0.2M Zn(OAc)2 was used as the electrolyte to construct a zinc-air battery power system.
[0070] In particular, the hydrogen production and desulfurization functional system is composed of an anode electrode, a cathode electrode, an anode cavity, a cathode cavity and a Na ion exchange membrane;
[0071] Furthermore, the anode electrode and the cathode electrode are fixed in the anode cavity and the cathode cavity respectively, and the anode cavity and the cathode cavity are separated by a Na ion exchange membrane;
[0072] Furthermore, 1 M NaOH was used as the cathode liquid, 1 M NaOH and 1 M Na2S simulated sulfur-containing wastewater were used as the anode liquid, and the Na ion exchange membrane was a Nafion 117 membrane;
[0073] In particular, the anode electrode and the cathode electrode are both FeMo2S4 / NiS X / NF-1, the preparation method thereof is as follows:
[0074] (1) Pretreatment of nickel foam (NF): Before use, the nickel foam with a thickness of 0.16 cm was cut into 1×1 cm -2 Rectangular piece;
[0075] At 3 mol L -1 The surface was ultrasonically treated in HCl solution, acetone, ethanol and deionized water for 30 minutes to remove the oxide layer, oil stains and residual impurities on the surface. Finally, it was vacuum dried at 60 °C and the surface showed a silver-grey metallic luster.
[0076] (2) Preparation of iron (II) oxide molybdenum / nickel foam (FeMoO4 / NF):
[0077] 400 mg (1.6 mmol) of sodium molybdate dihydrate and 300 mg (1.5 mmol) of ferrous chloride tetrahydrate were added to 40 mL of deionized water, ultrasonically dispersed (30 min) and stirred (20 min) to obtain a uniform solution containing iron and molybdate;
[0078] Then, the solution was transferred to a Teflon-lined stainless steel autoclave reactor (50 mL), the pretreated nickel foam (1) was placed vertically into the solution, the autoclave was sealed, and the reactor was kept at 130 °C in a convection oven for 5 h;
[0079] After the reaction is completed, cool to room temperature;
[0080] The nickel foam was removed and washed with deionized water and ethanol to remove residual salts and organic matter;
[0081] Finally, it was dried in a vacuum oven at 60 °C for 2.5 h to obtain the precursor product FeMoO4 / NF-1.
[0082] (3) Iron (II) molybdenum sulfide / nickel sulfide / nickel foam (FeMo2S4 / NiS X Preparation of NF-1:
[0083] Disperse 300 mg of sulfur-containing compound in 40 mL of deionized water;
[0084] The dispersed solution and FeMoO4 / NF were transferred to an autoclave reactor, sealed and placed in an oven for vulcanization treatment at 140 °C for 7 h.
[0085] After cooling naturally to room temperature, the sample was taken out and washed with deionized water and ethanol, and then dried under vacuum at 60 °C for 2.5 h to obtain the final product FeMo2S4 / NiS X / NF-1.
[0086] Synergistic engineering of Ni3S2@NiS(NiS X ) layered coupling interface, the optimized nanoflowers are conducive to the full contact between the electrolyte and the catalyst surface, increasing the number of electrocatalytic sites.
[0087] The X-ray diffraction (XRD) patterns were measured, such as Figure 4 As shown, FeMo2S4 / NiS X / NF-1 diffraction peaks are similar to those of FeMo2S4 (JCPDS#23-1118) and NiS X The diffraction peaks of (JCPDS#02-1280 / 44-1418) matched well, indicating the successful synthesis of the complex structure.
[0088] The FeMo2S4 / NiS prepared in this example was observed using a scanning electron microscope (SEM). X / NF-1 for microscopic morphology characterization, Figure 5 FeMo2S4 / NiS X / NF-1, it can be seen that FeMo2S4 / NiS X / NF-1 is a nano-microflower structure composed of nanosheets.
[0089] Specifically, the anode electrode of the functional system is connected to the zinc anode of the power system through a wire;
[0090] The cathode electrode of the functional system is connected to the air cathode of the power system through a wire.
[0091] Visualization of hydrogen collected by the drainage gas collection method (e.g. Figure 2 shown);
[0092] Only 4 mg of FeMo2S4 / NiS is used X / NF-1, a large amount of hydrogen (62.8 mL) can be rapidly produced within 100 min. Figure 7 It is calculated that the integrated system has 1.915mmolh -1 The high H2 yield is 7.89 mmol / min / g per gram of catalyst. catalyst These findings highlight the FeMo2S4 / NiS XThe excellent performance of NF as a trifunctional catalyst enables more efficient hydrogen production and more sustainable S resource recovery.
[0093] Comparative Example 1
[0094] The difference from Example 1 is that ferrous chloride tetrahydrate is not added:
[0095] FeMo2S4 / NiS was prepared as follows: X / NF-2:
[0096] (1) 750 mg (3.1 mmol) of sodium molybdate dihydrate was added to 40 mL of deionized water, and ultrasonically dispersed (30 min) and stirred (20 min) to obtain a uniform solution containing molybdate;
[0097] Then, the solution was transferred to a Teflon-lined stainless steel autoclave reactor (50 mL), the pretreated nickel foam was placed vertically into the solution, the autoclave was sealed, and the reactor was kept at 130 °C in a convection oven for 5 h;
[0098] After the reaction is completed, cool to room temperature;
[0099] The nickel foam was removed and washed with deionized water and ethanol to remove residual salts and organic matter;
[0100] Finally, it was dried in a vacuum oven at 60 °C for 2.5 h to obtain the precursor product FeMoO4 / NF-2.
[0101] (2) Dispersing 300 mg of the sulfur-containing compound in 40 mL of deionized water;
[0102] The dispersed solution and FeMoO4 / NF were transferred to an autoclave reactor, sealed and placed in an oven for vulcanization treatment at 140 °C for 7 h.
[0103] After cooling naturally to room temperature, the sample was taken out and washed with deionized water and ethanol, and then dried under vacuum at 60 °C for 2.5 h to obtain the final product FeMo2S4 / NiS X / NF-2.
[0104] XRD results show that FeMo2S4 / NiS X The diffraction peaks of / NF-2 are similar to those of NiMo2S4 (JCPDS#21-1273) and NiS X The diffraction peaks of (JCPDS#02-1280 / 44-1418) matched well, indicating the successful synthesis of the complex structure.
[0105] The microstructure of MoS2 / Ni9S8 / NF-2 prepared in this example was characterized by SEM at high magnification ( Figure 5 (b)) presents a nanorod-like structure with an irregular surface. Compared with the nanoflower-like structure composed of nanosheets in Example 1, the density of exposed active sites in Example 2 is reduced, which may reduce the electrocatalytic performance.
[0106] Comparative Example 2
[0107] The difference from Example 1 is that sodium molybdate dihydrate is not added:
[0108] FeMo2S4 / NiS was prepared as follows: X / NF-3:
[0109] (1) 616 mg (3.1 mmol) of ferrous chloride tetrahydrate was added to 40 mL of deionized water, and ultrasonically dispersed (30 min) and stirred (20 min) to obtain a uniform solution containing iron ions;
[0110] Then, the solution was transferred to a Teflon-lined stainless steel autoclave reactor (50 mL), the pretreated nickel foam was placed vertically into the solution, the autoclave was sealed, and the reactor was kept at 130 °C in a convection oven for 5 h;
[0111] After the reaction is completed, cool to room temperature;
[0112] The nickel foam was removed and washed with deionized water and ethanol to remove residual salts and organic matter;
[0113] Finally, it was dried in a vacuum oven at 60 °C for 2.5 h to obtain the precursor product FeMoO4 / NF-3.
[0114] (2) Dispersing 300 mg of the sulfur-containing compound in 40 mL of deionized water;
[0115] The dispersed solution and FeMoO4 / NF-3 were transferred to an autoclave reactor, sealed and placed in an oven for sulfurization treatment at 140 °C for 7 h.
[0116] After cooling naturally to room temperature, the sample was taken out and washed with deionized water and ethanol, and then dried under vacuum at 60 °C for 2.5 h to obtain the final product FeMo2S4 / NiS X / NF-3.
[0117] XRD results show that FeMo2S4 / NiS X The diffraction peaks of NF-3 are similar to those of FeNi2S4 (JCPDS#47-1740) and NiS X The diffraction peaks of (JCPDS#02-1280 / 44-1418) matched well, indicating the successful synthesis of the complex structure.
[0118] The FeMo2S4 / NiS prepared in this example was observed by SEM. X / NF-3 was characterized for microstructure at high magnification ( Figure 5 (c)) presents a nanorod flower-like structure, but it is worth noting that this nanoflower is relatively single. Compared with Example 1, the specific surface area of MoS2 / Ni9S8 / NF-1 may be improved, which further illustrates that the introduction of Mo is conducive to the improvement of the specific surface area, exposing more abundant catalytic active sites, and contributing to the improvement of the electrocatalytic performance.
[0119] Comparative Example 3
[0120] A commercial 20% platinum-carbon (Pt / C) catalyst was prepared according to the following steps.
[0121] 4 mg Pt / C powder (20%) was evenly dispersed in a mixture of 375 μL deionized water, 125 μL isopropanol and 20 μL Nafion, and ultrasonicated for 30 min. Then, 9.4 μL of ink was evenly dropped onto the surface of 1.5×1.0 cm carbon paper, and the electrode was dried at 80°C for 12 hours to obtain an electrode with 20% Pt / C.
[0122] Comparative Example 4
[0123] The nickel foam (NF) catalyst was treated according to the following steps.
[0124] Before use, commercially available nickel foam with a thickness of 0.16 cm was cut into 1×1 cm -2 Rectangular piece;
[0125] At 3 mol L -1 The samples were ultrasonically treated in HCl solution, acetone, ethanol and deionized water for 30 min to remove the oxide layer, oil stains and residual impurities on the surface. Finally, they were vacuum dried at 60 °C and the surface showed a silver-grey metallic luster.
[0126] Comparative Example 5
[0127] CuMoS / NiS was prepared according to the following steps X / NF catalyst.
[0128] (1) 400 mg (1.6 mmol) of sodium molybdate dihydrate and 256 mg (1.5 mmol) of cupric chloride dihydrate were added to 30 mL of deionized water, ultrasonically dispersed for 30 min and stirred for 20 min to obtain a uniform solution containing copper and molybdate;
[0129] Then, the solution was transferred to a Teflon-lined stainless steel autoclave reactor (50 mL), the pretreated nickel foam was placed vertically into the solution, the autoclave was sealed, and the reactor was kept at 130 °C in a convection oven for 5 h;
[0130] After the reaction is completed, cool to room temperature;
[0131] The nickel foam was removed and washed with deionized water and ethanol to remove residual salts and organic matter;
[0132] Finally, it was dried in a vacuum oven at 60 °C for 2.5 h to obtain the precursor product CuMoO / NF.
[0133] (2) Dispersing 300 mg of the sulfur-containing compound in 40 mL of deionized water;
[0134] The dispersed solution and CuMoO / NF were transferred to an autoclave reactor, sealed and placed in an oven for sulfurization treatment at 140 °C for 7 h.
[0135] After cooling naturally to room temperature, the sample was taken out and washed with deionized water and ethanol, and then dried under vacuum at 60 °C for 2.5 h to obtain the final product CuMoS / NiS X -NF.
[0136] Evaluation of electrocatalytic performance of each embodiment:
[0137] The SOR and HER performances were evaluated using a conventional three-electrode system: the prepared sample, platinum wire and Ag / AgCl were used as the working electrode, counter electrode and reference electrode, respectively; the performance of the catalyst in the example was evaluated using linear sweep voltammetry. The hydrogen evolution reaction (HER) activity was tested in a 1.0 M NaOH solution, and the sulfur oxidation reaction (SOR) activity was tested in a mixed solution of 1.0 M NaOH and 1.0 M Na2S. The results are shown in Figure 2. Figure 3 As shown and shown in Table 2 below.
[0138] Table 1
[0139]
[0140] It can be seen from Table 2 that FeMo2S4 / NiS X / NF-1 has excellent SOR and HER activities. As shown in the SEM images, FeMo2S4 / NiS X / NF-1 exhibits a nano-flower structure composed of nanosheets, thereby exposing more active sites, resulting in superior electrocatalytic performance. Compared with the synergistic effect of different elements under the same conditions, Cu and Mo synergistically engineered Ni3S2@NiS(NiS X )The hierarchical coupling interface exhibits poor HER performance and mediocre SOR performance, which once again illustrates the superiority of the synergistic engineering of Fe and Mo.
[0141] Example 2
[0142] Catalyst stability evaluation:
[0143] Evaluation of FeMo2S4 / NiS X The stability of the NF / MgO catalyst is the key to determine its feasibility for sustained practical application. We carefully tuned the interfacial interaction between the catalyst and the sulfide by introducing Mo, promoted the dissolution of the product sulfur on the electrode surface into the electrolyte, and converted it into long-chain polysulfides, effectively avoiding the passivation phenomenon.
[0144] As Figure 6 As shown, the stability of the sulfur oxidation reaction (SOR) was measured by 100 mA cm -2 The SOR potential was relatively stable with only slight fluctuations during the 480-h test, and the potential was basically restored to the initial state when the electrolyte was replaced with fresh electrolyte, indicating that the catalyst was minimally deactivated or passivated during the long catalytic process.
[0145] Likewise, for HER, the potential showed commendable stability over 480 h, as Figure 6 As shown, this indicates that FeMo2S4 / NiS X The Mg / Mg / NF catalysts have long-lasting stability. Therefore, this well-designed electrode material is expected to be an excellent candidate for efficient sulfur removal and hydrogen production.
[0146] Performance of hydrogen production and desulfurization system:
[0147] In the hydrogen production and desulfurization functional system, we measured the linear voltammetric curve of the two-electrode coupling system through an electrochemical workstation to evaluate its performance. Figure 7 As shown in Figure 2, only an ultra-low applied potential of 0.53 V is required to achieve 100 mA cm -2 The current density is much lower than the 1.895V usually required for traditional water electrolysis. Compared with traditional water electrolysis for hydrogen production, the energy consumption is reduced by about 28%, which is significantly lower than our previous report (0.64V) (DOI:10.1016 / j.jcis.2024.06.051). It is undoubtedly conducive to reducing energy consumption and improving the energy efficiency of the overall reaction, providing a solid guarantee for more efficient hydrogen production and more sustainable S resource recovery of the integrated self-driven system. In addition, the hydrogen production and desulfurization functional system also has advantages in energy equivalent input and reduction of carbon dioxide emissions, which is in line with the energy conservation and emission reduction principles advocated by carbon neutrality. Compared with the previous self-powered hydrogen production and desulfurization system, we have significantly reduced the external potential required for the coupling reaction of the hydrogen production and desulfurization functional system by upgrading the most core trifunctional catalyst, thereby achieving more efficient hydrogen production and more sustainable S resource recovery.
[0148] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. An improved self-powered system for synchronous and durable desulfurization and efficient hydrogen production, characterized by: The self-powered system comprises: A zinc-air battery self-power system (100) is composed of a zinc anode (101), an air cathode (102), an electrolytic cell (103) and an electrolyte (104); The hydrogen production and desulfurization functional system (200) is composed of an anode electrode (201), a cathode electrode (202), an anode chamber (203), a cathode chamber (204) and a Na ion exchange membrane (205), wherein NaOH is used as a cathode liquid, and NaOH and Na2S simulated sulfur-containing wastewater are used as an anode liquid; The zinc-air battery self-power system (100) generates a discharge current through an oxygen reduction reaction at an air cathode (102) and an oxidation reaction at a zinc anode (101), and drives a hydrogen production and desulfurization function system (200) to achieve hydrogen production and sulfur ion removal and resource recovery of S; The anode electrode (201) and the cathode electrode (202) are both FeMo2S4 / NiS X / NF materials, which have redox, sulfur oxidation and hydrogen evolution reaction activities; The air cathode (102) is made of FeMo2S4 / NiS X Prepared from powder.
2. The self-powered system according to claim 1, characterized in that: The FeMo2S4 / NiS X The preparation method of the / NF material comprises: Pretreatment of nickel foam: Cut the nickel foam with a thickness of 0.15-0.2 cm into 1×1 cm -2 Rectangular pieces, respectively, at 2~3molL -1 After ultrasonic treatment in HCl solution, acetone, ethanol and deionized water for 20 to 40 minutes, it was vacuum dried at 50 to 60°C until the surface showed a silver-grey metallic luster; Preparation of FeMoO4 / NF: 400 mg to 600 mg of molybdenum salt and 300 mg to 500 mg of iron salt were added to 30 mL to 50 mL of deionized water, ultrasonically dispersed for 20 to 30 min and stirred for 20 to 30 min to obtain a uniform solution containing iron and molybdate; The dispersed solution and the pretreated nickel foam were transferred to an autoclave reactor, the autoclave was sealed, and the temperature was kept at 130-160°C for 4-6 hours; After cooling naturally to room temperature, the nickel foam was taken out and washed with deionized water and ethanol, and then dried under vacuum at 40-60°C for 2-3h to obtain the precursor product FeMoO4 / NF; FeMo2S4 / NiS X Preparation of / NF: 300 mg to 500 mg of sulfur-containing compound is dispersed in 30 mL to 50 mL of deionized water; The dispersed solution and FeMoO4 / NF were transferred to an autoclave reactor, sealed and placed in an oven for vulcanization treatment at a constant temperature of 140-160°C for 6-8h; After cooling naturally to room temperature, the sample was taken out and washed with deionized water and ethanol, and then dried in vacuum at 40-60 °C for 2-3 h to obtain the final product FeMo2S4 / NiS X / NF.
3. The self-powered system according to claim 1, characterized in that: The FeMo2S4 / NiS X The preparation method of the powder comprises the following steps: X / NF was scraped and ultrasonically treated.
4. The self-powered system according to claim 1, characterized in that: The method for preparing the air cathode (102) comprises: FeMo2S4 / NiS X The powder was ultrasonically dispersed in a mixed solution of deionized water, isopropanol and Nafion to prepare ink; The ink is evenly dropped onto the surface of the hydrophobic carbon paper of the gas diffusion layer, and after drying, the air cathode of the zinc-air battery is obtained; Among them, FeMo2S4 / NiS X The ratios of powder, deionized water, isopropanol and Nafion solution were 15-25 mg: 360-380 μL, 120-140 μL and 10-20 μL, respectively.
5. The self-powered system according to claim 1, characterized in that: The zinc anode (101) is prepared by a method comprising grinding and polishing a zinc sheet with sandpaper to obtain an anode electrode of a zinc-air battery.
6. The self-powered system according to claim 5, characterized in that: The electrolyte (104) is a mixed solution of KOH and Zn(OAc)2, and the molar concentrations thereof are 5-7M and 0-1M, respectively.
7. The self-powered system according to claim 2, characterized in that: The iron salt is one or more of Fe(NO3)3·9H2O, FeCl3·6H2O, FeCl2·4H2O, and Fe2(SO4)3·9H2O; the molybdenum salt is K2MoO4, Na2MoO4·2H2O, (NH4)6Mo7O 24 ·One or more of 4H2O; the sulfur-containing compound is one or more of Na2S, C2H5NS, and CH4N2S.
8. The self-powered system according to claim 1, characterized in that: The NaOH and Na2S simulate sulfur-containing wastewater, wherein the volume molar concentration of the mixed solution of NaOH and Na2S is 0.5-1.5M.
9. The self-powered system according to claim 1, characterized in that: The NaOH is used as the cathode liquid, wherein the molar concentration of the NaOH solution is 0.5-1.5M, and the molar concentration of the Na2S solution is 0.5-1.5M.
